Analisis Strategi Pemasaran untuk Meningkatkan Daya Saing pada UMKM Marning Jagung Bapak Nuhadi - Ridho, Naufal Haydar; Sijabat, Yacobo Perdamaian (Transpublika Publisher, 2022)
The development of increasingly modern and sophisticated technology, causing increasingly fierce business competition, especially in the MSME sector in the food industry, makes business owners must be able to choose what kind of strategy will be carried out to encourage business development and be able to win the competition that occurs. The purpose of this study was to analyze marketing strategies to increase competitiveness in MSMEs corn marning Mr. Nuhadi. In this study, the author uses the SWOT analysis method. Data collection techniques in this study are surveys and interviews to collect data for MSME owners. The results of this study are MSME Mr. Nuhadi by conducting a SWOT analysis, the strategy that will be used is to increase business capital through programs provided by the government to add adequate tools and machines to continue to maintain product quality and maintain product image in the community. In order to meet market needs, the existing production scale will be added.